Cyclic nucleotide-gated ion channels. - Kaupp, U.B.; Seifert, R. (Physiological Reviews, 2002)
Cyclic nucleotide-gated (CNG) channels are nonselective cation channels first identified in retinal photoreceptors and olfactory sensory neurons (OSNs). They are opened by the direct binding of cyclic nucleotides, cAMP and cGMP. Although their activity shows very little voltage dependence, CNG channels belong to the superfamily of voltage-gated ion channels. Like their cousins the voltage-gated K+ channels, CNG channels form heterotetrameric complexes consisting of two or three different types of subunits. Six different genes encoding CNG channels, four A subunits (A1 to A4) and two B subunits (B1 and B3), give rise to three different channels in rod and cone photoreceptors and in OSNs. Important functional features of these channels, i.e., ligand sensitivity and selectivity, ion permeation, and gating, are determined by the subunit composition of the respective channel complex. The function of CNG channels has been firmly established in retinal photoreceptors and in OSNs. Studies on their presence in other sensory and nonsensory cells have produced mixed results, and their purported roles in neuronal pathfinding or synaptic plasticity are not as well understood as their role in sensory neurons. Similarly, the function of invertebrate homologs found in Caenorhabditis elegans, Drosophila, and Limulus is largely unknown, except for two subunits of C. elegans that play a role in chemosensation. CNG channels are nonselective cation channels that do not discriminate well between alkali ions and even pass divalent cations, in particular Ca2+. Ca2+ entry through CNG channels is important for both excitation and adaptation of sensory cells. CNG channel activity is modulated by Ca2+/calmodulin and by phosphorylation. Other factors may also be involved in channel regulation. Mutations in CNG channel genes give rise to retinal degeneration and color blindness. In particular, mutations in the A and B subunits of the CNG channel expressed in human cones cause various forms of complete and incomplete achromatopsia.